Annals of the disruption: with extracts from the narratives of ministers who left the Scottish establishment in 1843 - Brown, Thomas (Macniven & Wallace, 1892)
Appendices: 1. Disruption ministers, surviving and deceased.-- 2. List of Disruption manuscripts. -- 3. Showing the aggregate amount of funds raised by the Free Church during thirty-one years, from the disruption to 1873-74 inclusive. -- 4. Since the preceding list was drawn up as at 1st March, 1890, the following ministers have died.